2017
DOI: 10.1038/s41598-017-02208-y
|View full text |Cite|
|
Sign up to set email alerts
|

Spin-orbit-torque-induced magnetic domain wall motion in Ta/CoFe nanowires with sloped perpendicular magnetic anisotropy

Abstract: In materials with the gradient of magnetic anisotropy, spin-orbit-torque-induced magnetization behaviour has attracted attention because of its intriguing scientific principle and potential application. Most of the magnetization behaviours microscopically originate from magnetic domain wall motion, which can be precisely depicted using the standard cooperative coordinate method (CCM). However, the domain wall motion in materials with the gradient of magnetic anisotropy using the CCM remains lack of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…It has been shown that current-induced Oersted field has a non-negligible zcomponent at the edges of Hall-bar sample [56], which will further create a longitudinal domain wall in some cases [57]. It has also been shown by simulations that an effective out-of-plane field will be created by the magnetic anisotropy gradient, which can be utilized to drive domain wall motion [58,59]. Therefore, we postulate that the current that we applied will first create a longitudinal domain wall in the sample, and then the magnetization switching will be achieved by lateral domain wall motion, which is driven by the transverse magnetic anisotropy gradient.…”
Section: Field-free Current-induced Switchingmentioning
confidence: 99%
“…It has been shown that current-induced Oersted field has a non-negligible zcomponent at the edges of Hall-bar sample [56], which will further create a longitudinal domain wall in some cases [57]. It has also been shown by simulations that an effective out-of-plane field will be created by the magnetic anisotropy gradient, which can be utilized to drive domain wall motion [58,59]. Therefore, we postulate that the current that we applied will first create a longitudinal domain wall in the sample, and then the magnetization switching will be achieved by lateral domain wall motion, which is driven by the transverse magnetic anisotropy gradient.…”
Section: Field-free Current-induced Switchingmentioning
confidence: 99%
“…Heff includes the effective fields contributed from exchange coupling in every FM layer, the interlayer RKKY exchange coupling, the magnetic anisotropy energy, the demagnetization energy, and the DMI. H SO is the effective field of the SOT, and it is expressed as [15]:HSO=μBθSHJ/γ0normaleMSLz…”
Section: Methodsmentioning
confidence: 99%
“…All the parameters used in our simulation are in an experimentally achievable range. Without loss of generality, we applied a positive DMI constant and a positive spin-Hall angle that ensures the motion of a right-handed DW against the direction of the current (along the direction of electron flow) [15]. The change of the sign of DMI or the spin Hall angle only reverses the motion direction of the DW but does not influence the conclusion of this paper.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavy metal layer leads to a perpendicular magnetic anisotropy (PMA) in the CoFeB layer, and a Dzyaloshinskii-Moriya interaction (DMI) which stabilizes chiral domain walls. In order to achieve controlled positioning of the DW we propose current clocked DW motion in conjunction with a gradient in the PMA [24,25]. Notches are placed at regular intervals to arrest the DW at different locations of the racetrack.…”
Section: Introductionmentioning
confidence: 99%